Reconstruction of Intersection the Customary Court and State Criminal Court for Indigenous Communities in Papua - Suhariyanto, Budi; Mulyadi, Lilik; Afandi, Fachrizal; Muhammad S.R.P., Sri Gilang (Journal of Indonesian Legal Studies, 2024)
The Law on Special Autonomy for Papua Province grants the Customary Court the authority to adjudicate criminal cases involving indigenous Papuans. Parties dissatisfied with the decisions of the Customary Court may appeal to the State Court. However, conflicts arise when the formal criminal justice system intervenes before the customary resolution process is completed, creating jurisdictional clashes. This raises the question of how to harmonize the relationship between these two judicial systems in a manner that fosters accommodation rather than resistance. This study employs both document analysis and field research, including interviews with law enforcement officials, judges, academics, and traditional leaders in Jayapura and Manokwari. The findings reveal that the intersection between the Customary Court and the State Court is inevitable, as the subject matter, object, and principles of criminal responsibility overlap between the two systems. To mitigate conflicts, a reconstruction of the interaction between Customary Courts and State Courts is essential, particularly in the adjudication of criminal cases involving customary law communities. Key strategies include fostering synergy and aligning perceptions between the apparatus of the Customary and State Courts. Additionally, the development of comprehensive guidelines for handling customary crime cases is crucial. Such guidelines would provide judges operating within Papua’s jurisdiction with a clear framework for considering customary law, thereby promoting integration and mutual respect between the two judicial systems. This approach aims to ensure that both customary and state legal traditions coexist harmoniously within the context of Papua’s special autonomy.